Omega‐3 supplementation improves cognition and modifies brain activation in young adults. (28th January 2014) - Bauer, Isabelle; Hughes, Matthew; Rowsell, Renee; Cockerell, Robyn; Pipingas, Andrew; Crewther, Sheila; Crewther, David
<x xml:space="preserve">Abstract</x> Objective The current study aimed to investigate the effects of eicosapentaenoic acid (EPA)‐rich and docosahexaenoic acid (DHA)‐rich supplementations on cognitive performance and functional brain activation. Design A double‐blind, counterbalanced, crossover design, with a 30‐day washout period between two supplementation periods (EPA‐rich and DHA‐rich) was employed. Functional magnetic resonance imaging scans were obtained during performance of Stroop and Spatial Working Memory tasks prior to supplementation and after each 30‐day supplementation period. Results Both supplementations resulted in reduced ratio of arachidonic acid to EPA levels. Following the EPA‐rich supplementation, there was a reduction in functional activation in the left anterior cingulate cortex and an increase in activation in the right precentral gyrus coupled with a reduction in reaction times on the colour–word Stroop task. By contrast, the DHA‐rich supplementation led to a significant increase in functional activation in the right precentral gyrus during the Stroop and Spatial Working Memory tasks, but there was no change in behavioural performance. Conclusions By extending the theory of neural efficiency to the within‐subject neurocognitive effects of supplementation, we concluded that following the EPA‐rich supplementation, participants' brains worked 'less hard' and achieved a better cognitive performance than prior to supplementation. Conversely, the increase in functional activation and lack of improvement in time or accuracy of cognitive performance following DHA‐rich supplementation may indicate that DHA‐rich supplementation is less effective than EPA‐rich supplementation in enhancing neurocognitive functioning after a 30‐day supplementation period in the same group of individuals. Copyright © 2014 John Wiley & Sons, Ltd.